METHODS OF REINFORCEMENT – IMPLICATIONS IN THE OPTIMIZATION OF COMPLETE DENTURE IN ACCORDANCE WITH CLINICAL PARTICULARITIES - Irina Gradinaru; Cristina Gena Dascalu; Magda Ecaterina Antohe (Romanian Journal of Oral Rehabilitation, 2019)
The clinical reality of the total edentation from the point of view of the impact on the general condition of the patient, with extremely serious disturbances on the body pattern, correlated with the variety of clinical situations, always impregnated by the current social aspects, are only a few elements that advocate optimizing the total prosthesis structure by different reinforcement methods. The aim of the study is the practical materialization of the possibilities of optimization of the parameters of totally removable prostheses by associating the types of acrylate with the method of reinforcement with polyethylene fibers and metal nets. Material and method :A total of 12 specimens were made in the form of thin rectangular plates with a longitudinal dimension of 40 mm, a width of about 20 mm, having a thickness ranging from 1.8 to 2.5.Biomechanical tests were done on a HEKERT 50 machine (on a 10 kN scale) and on a Textenser test machine (500N maximum force).The test specimens have combined the different types of acrylate used in dental practice by associating it with various forms of reinforcement, represented by metal nets, respectively polyethylene fibers. Results and discussions: After the examination of the traction patterns of the traction specimens, the following aspects were noted: Unarmed materials showed cross-sectional sections, slightly corrugated with respect to the direction of force. The armed (asymmetric) materials yielded to areas without reinforcement (cracks usually starting from the hole made at the gripping ends). The cracks produced in the reinforcing areas had the following directions: transverse to the reinforcing fibers: I (acrylate and randomly arranged polyethylene fibers), II (acrylate, longitudinally disposed polyethylene fibers), III (acrylate, metal mesh). Conclusions: In the optimization of the therapeutic solutions excellent results are obtained in case of reinforcement with polyethylene fibers longitudinally disposed. It is known that the clinical particularity dictates the final design of the total prosthesis, so in the case of patients with muscular hypertonia, the optimal therapeutic solution remains the reinforcement with polyethylene fibers due to the very good adherence of the polyethylene fibers to the acrylate followed by the metal mesh reinforcement.